Comparison of DNA Extraction Methods for the Detection of Canned Tuna Species with DNA Mini-Barcoding - Aubrey J. Emmi; Biola Fatusin; Rosalee S. Hellberg (Journal of Food Quality)
Tuna is susceptible to species mislabeling due to its high demand, quick rate of production, and wide range of price points. DNA barcoding, a sequencing-based technique, allows for the detection of species mislabeling by targeting a standardized region of DNA. A mitochondrial control region (CR) DNA barcode has been found to be capable of species discrimination for tuna, but it is challenging to recover the entire DNA fragment from canned tuna. While a short fragment of CR, referred to as a “mini-barcode,” has shown some success with canned tuna species identification, more research is needed to improve identification rates. The objective of this study was to determine the optimal DNA extraction method for species identification of canned tuna using CR mini-barcoding. Four commercial DNA extraction kits were compared using a sample set of 24 different cans of tuna labeled as albacore, light tuna, skipjack, or yellowfin. All samples were tested in duplicate. The greatest success was found using the Qiagen DNeasy Blood and Tissue Kit and the Qiagen DNeasy Mericon Food Kit, which resulted in species identification for 42% of the samples. In comparison, the MP Biomedicals FastPrep-24 + Machery-Nagel NucleoSpin Tissue Kit resulted in species identification for 30% of the samples and the Qiagen DNeasy Blood and Tissue Kit + PowerClean Pro Cleanup Kit resulted in species identification for 21% of the samples. Overall, the top-performing DNA extraction methods for use with CR mini-barcoding of canned tuna products were determined to be the DNeasy Blood and Tissue Kit and the DNeasy Mericon Food Kit.